Pollutant concentrations in rime and fog water - Jaroslav Fišák; Miroslav Tesař; Daniela Fottová (Soil and Water Research, 2008)
: The present study deals with a comparison between the pollutant concentrations in the samples of rime and of fog water (so-called deposited or occult precipitation) collected at the Milešovka Observatory. Although rime can be observed during a limited part of the year, it still has an important share in the total amount of precipitation and can contribute significantly to a local increase in pollutant loads. The total sum of the selected free ions in the rime water represents approximately a half of the total sum of the selected free ions in the fog water. The relative contents of free ions in the mean sample were different in rime and fog water with the exception of K+, Mg2+ and F- that did not show any significant variations.